Environmental & architectural phenomenology. Vol. 3, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 1992)
Vol. 3, No. 3, Fall 1992 (includes “items of interest,” "citations received,” article and book commentaries, movie review of Places for the Soul, and poem by John Sherry).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals